A CASE OF MENINGEAL MELANOMATOSIS. Issue 10 (9th September 2014) - Ghadiri-Sani, Mona; Enevoldson, Peter
Abstract : Background: Primary diffuse meningeal melanomatosis is a rare form of CNS melanoma arising from the melanocytes within the leptomeningies with very poor prognosis. Case presentation: A 32 year old man presented with multiple transient alternating lower leg sensory and motor symptoms, headaches and seizures. He had papilloedema and asymmetrical pyramidal signs in the lower legs. MRI scan revealed a para-sagittal high signal in the medial surface of the left frontal lobe. Lumbar puncture confirmed an elevated pressure and a mildly raised protein but normal cell counts and cytology. CTV and DSA showed a filling defect in the superior sagittal sinus, compatible with thrombus. He was anticoagulated, and then suffered a large right frontal bleed (despite anticoagulation within therapeutic range). Heparin was discontinued but a further bleed occurred nevertheless. Progressive drowsiness led to a non-lesional and meningeal biopsy which revealed Meningeal Melanomatosis, for which no specific treatment was thought possible. He died about 10 weeks after first presentation. Conclusion: We present a case of fatal meningeal melanomatosis which masqueraded as a superior sagittal sinus thrombosis. Imaging and photographs from the brain biopsy will support the case.